REVITALISASI STASIUN BESAR YOGYAKARTA DENGAN PENDEKATAN ARSITEKTUR KONTEKSTUAL - Sakti Randhy Saputra; Agus Heru Purnomo; Samsudi Samsudi (Universitas Sebelas Maret Surakarta, 2016)
The development of rail transport is increasing every year, it can be seen in the annual report of PT. KAI 2014 with passenger volume increase of 26% from 2013. Yogyakarta Station is located in the center of Yogyakarta that was built in 1887, became the largest station in Yogyakarta by serving a variety of class trips with destination cities in Java. Yogyakarta station currently require development to support the development of rail transport. Contextual Architecture is used as an architectural design approach for prioritizing Contextual visual linkage between the new buildings with the old building. The problems that arise in the design of this is how to maintain a visual connection between the old station buildings with new buildings that require a larger space either facade or mass laying in it. The process of creative thinking methods into methods of designing process Yogyakarta Station's revitalization. Revitalization Yogyakarta Station is done with development facilities with the construction of new buildings, so as to maintain the interconnection visual, processing performed facade on a new mass behind old buildings with elements of old buildings such as the rhythm of the windows, doors, pediment and also the color of the material. Kata kunci: Creative Thinking, Contextual Architecture, Revitalitation, Train.